Peningkatan Pengetahuan Remaja dalam Mereduksi Stigma Orang Dengan Gangguan Jiwa (ODGJ) Melalui Edukasi - Triyana Harlia Putri; Yuyun Tafhwidah; Fitri Fujiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
ODGJ becomes difficult in the healing process caused by the high community stigma including the adolescents group. Even so, youth is one of the golden periods where information becomes important and easy to apply if education is provided, especially regarding the stigma of ODGJ. Based on this, there is a need for promotive efforts to increase youth knowledge about ODGJ and Stigma, so that it can reduce stigma, discrimination, violation of human rights in ODGJ. The purpose of carrying out this activity is to increase youth's knowledge regarding ODGJ and Stigma. This activity was held on March 2023 at SMPN 5 Pontianak City. The method used is in the form of counseling followed by educational videos and distribution of ODGJ stigma pocket books. The form of evaluation used is using knowledge instruments before and after education. Community service activities report an increase in youth's knowledge of ODGJ and stigma. The results of the analysis found that there was a significant impact on ODGJ education and stigma on increasing knowledge p-value = 0.011. It is hoped that with this increased knowledge, youth can provide information again and change wrong perceptions about ODGJ.